Assessing probabilistic hazard and risk for building, road network, and ecosystems: the case study of La Florida municipality, Galeras Volcano, Colombia - G. A. Córdoba; G. A. Córdoba; A. Costa; D. M. Rodriguez; J-C. Thouret; R. A. Criollo; D. A. Guerrero; D. A. Guerrero (Frontiers in Earth Science)
Volcanic activity can cause severe damage to buildings, transport networks, ecosystems, and critical infrastructure, making quantitative approaches that integrate hazard, exposure, and vulnerability essential for informed decision-making. This study introduces the Volcanic Risk Metric (VRM), a systematic framework for volcanic risk quantification, aligned with the National Guide for Risk Analysis and the Sendai Framework for Disaster Risk Reduction, and applies it to La Florida Municipality, Colombia, part of which lies within the high-hazard zone of Galeras Volcano. Probabilistic hazard curves were generated for each pixel of a digital elevation model and combined with vulnerability curves tailored to buildings, road networks, and ecosystems. For each hazard–asset pair, a risk curve was calculated and multiplied by the replacement cost of the asset to estimate expected physical loss. By identifying, for each pixel, the maximum risk value among all hazards, an integrated volcanic risk map was developed, highlighting zones of greatest expected loss, particularly in areas with dense infrastructure and population within the volcano’s high-hazard zone. This map provides valuable information for planning, mitigation, and emergency response in La Florida Municipality, and the VRM approach is transferable to other volcanic regions, offering a practical tool for risk-informed land-use planning and enhancing disaster resilience.